Design and fabrication of auxetic PCL nanofiber membranes for biomedical applications - Bhullar, Sukhwinder Kaur; Rana, Deepti; Lekesiz, Hüseyin; Bedeloğlu, Ayşe; Ko, Junghyuk; Cho, Yonghyun (Elsevier, 2017)
The main objective of this study was to fabricate poly (e-caprolactone) (PCL)-based auxetic nanofiber membranes and characterize them for their mechanical and physicochemical properties. As a first step, the PCL nanofibers were fabricated by electrospinning with two different thicknesses of 40 pm (called PCL thin membrane) and 180 pm (called PCL thick membrane). In the second step, they were tailored into auxetic patterns using femtosecond laser cut technique. The physicochemical and mechanical properties of the auxetic nanofiber membranes were studied and compared with the conventional electrospun PCL nanofibers (non-auxetic nano fiber membranes) as a control. The results showed that there were no significant changes observed among them in terms of their chemical functionality and thermal property. However, there was a notable difference observed in the mechanical properties. For instance, the thin auxetic nanofiber membrane showed the magnitude of elongation almost ten times higher than the control, which clearly demonstrates the high flexibility of auxetic nanofiber membranes. This is because that the auxetic nanofiber membranes have lesser rigidity than the control nanofibers under the same load which could be due to the rotational motion of the auxetic structures. The major finding of this study is that the auxetic PCL nanofiber membranes are highly flexible (10-fold higher elongation capacity than the conventional PCL nanofibers) and have tunable mechanical properties. Therefore, the auxetic PCL nanofiber membranes may serve as a potent material in various biomedical applications, in particular, tissue engineering where scaffolds with mechanical cues play a major role.
Keywords: Electrospinning; Auxetic nanofiber membranes; Poly (epsilon-caprolactone); Mechanical behavior; Biomedical applications